The Impact of Peach Rootstocks and Winter Cover Crops on Reproduction of Ring Nematode - Sagar GC; Ivan Alarcon-Mendoza; David Harshman; Churamani Khanal (Plants, 2024)
Two peach rootstocks (‘Guardian’ and ‘MP-29’) and ten winter cover crops (rye, wheat, barley, triticale, oat, Austrian winter pea, crimson clover, balansa clover, hairy vetch, and daikon radish) were evaluated in a greenhouse environment to determine their suitability to host ring nematode, Mesocriconema xenoplax. Each crop was inoculated with 500 ring nematodes, and the experiments were terminated 60 days after inoculation. The reproduction factor (ratio of final and initial nematode population) ranged from 0 to 13.8, indicating the crops greatly varied in their host suitability to ring nematode. ‘Guardian’ has been known to tolerate ring nematode; however, results from the current study suggest the tolerance statement is anecdotal. Another peach rootstock, ‘MP-29’, was also a good host for ring nematode, suggesting an urgency to develop ring nematode-resistant peach rootstocks. Wheat supported the least to no nematode reproduction while pea supported the greatest reproduction. The rest of the cover crops were poor to good hosts to ring nematodes. Although planting cover crops in peach orchards is not common, employing non or poor host crops can help suppress nematodes in addition to having soil health benefits. Furthermore, peach breeding programs should focus on finding and introgressing ring nematode resistance in commercial rootstocks.